Fashion and Feeling
XVI, 337 p. 19 illus., 15 illus. in color.
Keywords: Fashion and Feeling: The Affective Politics of Dress explores the complex nexus of fashion and the feeling body from a variety of critical perspectives across fashion studies, anthropology, sociology, design practice, and media studies. It asks such questions as: What does fashion look and feel like in an age dominated by amplified anxiety, isolation, depression, and precariousness? How are feelings woven into clothing and mobilized through fashion practices in ways that might sustain living with a sense of ongoing crisis? Does fashion have the potential to help us reimagine new lifeworlds which might be reinvigorating? In other words, how is fashion engaging with the “bad,” the “good,” and the ambivalent feelings associated with our personal and collective histories, with our troubled political present, and with our imagined future? Despite such diverse and scattered contributions, the potentialities of “feeling” for the study of fashion arestill largely neglected. This edited volume seeks to tease out possible avenues of investigation of the clothed body and its representations through the lens of feeling. Roberto Filippello is a Killam Postdoctoral Research Fellow and a Teaching Fellow in Gender Studies at the University of British Columbia, Okanagan, Canada. Ilya Parkins is Associate Professor of Gender, Women and Sexuality Studies at the University of British Columbia, Okanagan, Canada.